Validation of the Personal Resources Construct among Women Academics Using Covariance-Based Structural Equation Modeling (CB-SEM) - Verica Sofie; Herdian Herdian; Retno Dwiyanti (The Future of Education Journal, 2026)
Personal resources are psychological capacities that enable individuals to cope effectively with work-related demands and multiple role responsibilities. This study aimed to evaluate the construct validity and reliability of a personal resources instrument developed for female academics using Confirmatory Factor Analysis (CFA) within a Covariance-Based Structural Equation Modeling (CB-SEM) framework. A total of 128 female academics participated in the study. The initial instrument consisted of 20 items representing four dimensions, namely self-efficacy, optimism, resilience, and personal control. Content validity was assessed using Aiken’s V, while construct validity was evaluated through SmartPLS 4. The results indicated that all items achieved acceptable content validity, with Aiken’s V values ranging from 0.75 to 1.00. Initial CFA results revealed inadequate model fit, resulting in the elimination of indicators with low factor loadings. The final model consisted of three dimensions—self-efficacy, optimism, and resilience—with nine retained indicators. The revised model demonstrated acceptable fit indices (χ²/df = 2.284; SRMR = 0.049; GFI = 0.918; TLI = 0.903; CFI = 0.935), and all indicators showed factor loadings above 0.50. Construct reliability was satisfactory, while convergent validity was supported for optimism and resilience and remained marginal for self-efficacy. Overall, the findings suggest that the instrument possesses an adequate factor structure and can be used to assess personal resources among female academics.